2019
DOI: 10.1111/jan.14125
|View full text |Cite
|
Sign up to set email alerts
|

The experience of partners supporting adolescents and young adults with cancer

Abstract: Aims In a larger study where the aim was to investigate choice and control in decision making, the role of partners was significant. Reported here are the experiences of those partners of young people with cancer. Design A qualitative, exploratory case study approach was used. Methods In the larger study, 22 participants were recruited including five adolescents and young adults with cancer, two sets of parents/carers and three individual parents, five healthcare professionals linked to the adolescent or young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Life Interrupted echoes previous studies involving AYA living with other cancers (Davies et al, 2015, 2018, 2019; Grinyer, 2007; Soanes & Gibson, 2018; Woodgate, 2006; Zebrack et al, 2014). However, our study's multi‐perspective focus on the specific experiences of AYA and their families living with MM raised three important considerations: public awareness and education, being an AYA and age‐appropriate care and future research.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Life Interrupted echoes previous studies involving AYA living with other cancers (Davies et al, 2015, 2018, 2019; Grinyer, 2007; Soanes & Gibson, 2018; Woodgate, 2006; Zebrack et al, 2014). However, our study's multi‐perspective focus on the specific experiences of AYA and their families living with MM raised three important considerations: public awareness and education, being an AYA and age‐appropriate care and future research.…”
Section: Discussionsupporting
confidence: 73%
“…Thirdly, research into AYAs with cancer has focused on the more common forms of cancers, such as leukaemia, hodgkin's lymphoma and bone cancer with MM being understudied (Davies el al., 2018, 2019; Fern et al, 2013; Lavender et al, 2019; , Pearce et al, 2020; Taylor et al, 2013; Zebrack et al, 2014). Research by Lavender et al, (2019), through a narrative inquiry with health professionals, explored one specific cancer and how AYAs were prepared for inclusion in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that partners, as well as parents, tended to put aside their own needs and fully devote themselves to caregiving [ 20 , 26 , 35 , 41 ]. They also tended not to show their worries and emotions to the patient or other family members, as there was a frequent dread of inciting the same fear or worry in others, as well [ 19 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Activities of daily living were often shifted to the caregivers, including providing help with the washing, dressing, and transportation of the patient [ 18 , 21 , 39 ], administering drugs and food, managing and planning hospital visits, providing emotional support [ 17 , 19 , 20 , 21 , 39 , 44 ], and attending and advocating during visits to the healthcare professional [ 19 , 20 , 21 , 24 , 26 , 39 ]. Caregivers also assisted their patient in making difficult medical decisions [ 17 , 41 ], searched for specific information to pass on to the patient [ 19 , 42 ], took care of their children, as the patient often did not have the time or energy [ 42 ], and actively managed manifestations and signs of the disease [ 21 , 39 ]. In addition, mothers with caregiver duties helped to arrange plans for the AYAs’ future, such as for work, housing, or insurance [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation